PENINGKATAN KEMAMPUAN MENYIMAK CERITA ANAK DENGAN METODE LATIHAN SISWA KELAS I SDN 006 PAGARAN TAPAH DARUSSALAM - Eny Maradonah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by the low ability class I listened to stories of children SDN 006 Pagaran Tapah Darussalam. Goals to be achieved in this research is to improve the ability to listen to stories of children of class I SDN 006 Pagaran Tapah Darussalam through student training methods implemented during one month. This research was conducted in SDN 006 Pagaran Tapah Darussalam. Classes are meticulous researcher is Class 1 by the number of students as many as 25 people. The study of this class action commenced in early February 2016. This form of research is classroom action research. The research instrument consists \ of instruments teacher and student activity sheets and achievement test. Based on the research, the conclusion of the research is to improve the ability to listen to stories of children with methods of training students in grade I SDN 006 Pagaran Tapah Darussalam. On average students at the beginning of the test is average with the average value of 63.20 and the first cycle increased to 67.20 with high category, while in the second cycle of average ability students categorized as good with the average value of 82, but with completeness 96%, where the value of the student has achieved mastery. The above statement shows that the students' ability of listening to stories of children with methods of training students in grade I SDN 006 Pagaran Tapah Darussalam. can be enhanced through training methods. Thus the research hypothesis that read "Upgrades Listening to the stories of children with methods of training students in grade I SDN 006 Pagaran Tapah Darussalam" "acceptable"